The Development of Learning Activities Using the Open Approach Combined with the SSCS Model to Enhance Mathematical Problem-Solving Ability on Statistics among Grade 8 Students - Pansood, Siriwan; Lincharoen, Aumporn (Journal of Buddhist Education and Research (JBER), 2025)
This research aimed to develop and evaluate the effectiveness of learning activities using the Open Approach integrated with the SSCS model to enhance Grade 8 students’ mathematical problem-solving abilities on the topic of statistics. It also examined students’ behaviors during the learning process, compared their problem-solving abilities before and after the intervention, and assessed their satisfaction with the learning experience. The sample consisted of 35 Mathayomsuksa II students selected through cluster random sampling from Khlong Khlung Rat Rangsan School during the second semester of the 2024 academic year. The research instruments included a set of learning activities, a mathematical problem-solving test, a field observation form, and a student satisfaction questionnaire. The statistics used were content analysis, mean, standard deviation, and dependent t-test. The learning activities were developed in four phases: presenting open-ended problems, facilitating student-centered problem-solving, encouraging classroom discussion and idea comparison, and summarizing key mathematical concepts. The overall appropriateness of the activities was rated at the highest level (x̄ = 4.67, S.D. = 0.58), and the effectiveness score (77.41/76.00) met the established criterion (75/75). Observations showed continuous development in students’ problem-solving skills. Post-test scores were significantly higher than pre-test scores (p < .05), indicating the positive impact of the activities. Additionally, students reported high satisfaction with the learning process (x̄ = 4.34, S.D. = 0.47). suggesting that the Open Approach with SSCS effectively promoted engagement and mathematical thinking.